2015
DOI: 10.1155/2015/591707
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Impairment of Quality of Joint Motion in Vibroarthrographic Signal Analysis

Abstract: Aging is associated with degenerative changes in articular surfaces leading to quantitative and qualitative impairment of joint motion. Therefore, the aim of this study is to evaluate an age-related quality of the patellofemoral joint (PFJ) motion in the vibroarthrographic (VAG) signal analysis. Two hundred and twenty individuals were enrolled in this study and divided into five groups according to age. The VAG signals were collected during flexion/extension knee motion using an acceleration sensor and describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Hence, the authors suggest a role for more sensitive and responsive diagnostic techniques in the assessment of mild and moderate disorders. One of these methods for direct analysis of crepitations could be vibroarthrography (VAG), which seems to support physical examination for objective assessment of quality of joint motion [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the authors suggest a role for more sensitive and responsive diagnostic techniques in the assessment of mild and moderate disorders. One of these methods for direct analysis of crepitations could be vibroarthrography (VAG), which seems to support physical examination for objective assessment of quality of joint motion [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the AE signals were measured by attaching sensors to the medial epicondyle of the tibia, the lateral epicondyle of the tibia, and the front of the patella in the same position as the previous studies. (19)(20)(21)(22) Two IMU sensors were also attached to the thigh and the tibia to calculate knee joint angle because an IMU sensor has the advantages of low price, small size, and light weight, unlike camera-based motion analysis systems. Baczkowics et al (21) analyzed AE signals in normal knee and chondromalacia patients during knee flexion and extension.…”
Section: Discussionmentioning
confidence: 99%
“…(19)(20)(21)(22) Two IMU sensors were also attached to the thigh and the tibia to calculate knee joint angle because an IMU sensor has the advantages of low price, small size, and light weight, unlike camera-based motion analysis systems. Baczkowics et al (21) analyzed AE signals in normal knee and chondromalacia patients during knee flexion and extension. The results indicated that the amplitude of the AE signal was larger in the patients compared to those in the normal group, and frequencies were confirmed in the 100 Hz-1 kHz range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knee OA mainly occurs in the elderly (Shamir et al, 2009). About 30% of people over the age of 65 suffer from knee OA (Bączkowicz, Majorczyk, & Kręcisz, 2015). Moreover, the incidence of knee OA is higher in females than in males, and its possibility increases with age.…”
Section: Introductionmentioning
confidence: 99%